2015
DOI: 10.12816/0017710
|View full text |Cite
|
Sign up to set email alerts
|

Corruption in Nigeria : An Examination of Failed National Assembly Probes

Abstract: Nigeria is a country reputed for its high corruption index, the activities of the multinational oil companies have always been reported to be in shortfall of globally accepted best practices and transparency. Matters are not helped by a perceivably corrupt agency in charge of supervising the oil and gas industry, the Nigeria National Petroleum Corporation (NNPC). The Nigeria Extractive Industry Transparency Initiative (NEITI) has had cause in the recent past, to accuse the oil majors of irregularities in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In fact, the 3rd respondent is of the view that the antigraft agencies themselves sometime aid corruption. In a like manner, Onuigbo (2015) observed that, the creation of Economic and Financial Crimes Commission (EFCC), Independent Corrupt Practices and other related Commission (ICPC), as well as the Code of Conduct Bureau and its tribunal, though, has registered little success, but they have gone after the tail of the monster of corruption rather than its heads. Moreover, Otusanya, at, el., (2015) find out that, one of the implications of an elite financial crime is the inability of the regulators to effectively apprehend the legislators in corrupt practices, because the present regulatory institutional apparatus are not well equipped in dealing with financial crime of the legislature.…”
Section: The Nature Of Legislative Corrupt Practices In Nigeriamentioning
confidence: 99%
“…In fact, the 3rd respondent is of the view that the antigraft agencies themselves sometime aid corruption. In a like manner, Onuigbo (2015) observed that, the creation of Economic and Financial Crimes Commission (EFCC), Independent Corrupt Practices and other related Commission (ICPC), as well as the Code of Conduct Bureau and its tribunal, though, has registered little success, but they have gone after the tail of the monster of corruption rather than its heads. Moreover, Otusanya, at, el., (2015) find out that, one of the implications of an elite financial crime is the inability of the regulators to effectively apprehend the legislators in corrupt practices, because the present regulatory institutional apparatus are not well equipped in dealing with financial crime of the legislature.…”
Section: The Nature Of Legislative Corrupt Practices In Nigeriamentioning
confidence: 99%